Sludge baking-free building block and preparation method thereof
Through the coordinated alkali excitation technology of blast furnace slag and fly ash and the optimization of raw material ratio, the problems of low strength, long production cycle and high cost of sludge blocks are solved, and the rapid self-consolidation and performance improvement of sludge are achieved, which meets the high Standard block performance requirements.
Patent Information
- Application Number
- CN202411491356.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-07
AI Technical Summary
In the existing sludge block technology, the organic matter and heavy metals in the sludge cannot be effectively cured, and the prepared blocks are low in strength, long in production cycle and high in cost.
Through the synergistic alkali excitation technology of blast furnace slag and fly ash, the silicon-aluminum minerals in blast furnace slag and fly ash are quickly dissolved under a strong alkaline environment, releasing metal cations, and attacking the inert silicon-aluminum mineral bonded to oxygen in the sludge in the sludge , reduce its binding energy and achieve rapid self-consolidation of sludge. At the same time, by adjusting the ratio of sludge, blast furnace slag, fly ash, and machined sand, the grading of raw materials is optimized to make the burn-free blocks more dense.
It realizes rapid self-consolidation of sludge in a burn-free state, improves the compression, flexural and freezing properties of the block, and meets the highest grade mark in "JC/T 422-2007 Non-sintered waste tailings bricks" MU25 standard reduces production costs and cycles.
Smart Images

Figure CN119390421A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of unfired building blocks, and in particular to a sludge unfired building block and a preparation method thereof. Background Art
[0002] Silt contains rich sediments, organic and inorganic components, high water content, low strength, poor permeability, high compressibility, and a pungent odor. Silt cleaning is crucial to increasing the depth of waterways, improving water quality, and repairing ecosystems. Currently, most silt is backfilled or directly covered nearby. Large amounts of silt storage not only occupy land resources, but also pose potential problems such as secondary diffusion of pollutants, land use conflicts, and soil eutrophication.
[0003] Masonry blocks are man-made blocks made of concrete, industrial waste (slag, fly ash, etc.) or local materials. They are larger in size than bricks, have the advantages of simple equipment and fast masonry speed, and meet the requirements of wall reform in the development of building industrialization. Unfired masonry blocks have a wide range of raw materials and are sinter-free and steam-free, and are widely used in the wall material construction industry. Using sludge as the raw material for unfired masonry blocks can not only effectively save resources, reduce energy consumption and costs, but also absorb a large amount of sludge and solve environmental pollution problems.
[0004] There are two main aspects of the existing silt block technology: one is the sintering method, in which the silt is dehydrated and added with other solid wastes (fly ash, tailings) for modulation, and then pressed into shape and sintered at above 1050°C, such as a lake silt sintered brick and preparation method (CN115286421A), and a method for preparing sintered bricks by high-temperature roasting of river silt (CN116715507A). Although the blocks made by the sintering method do not require a long-term curing process and the addition of cement, they consume a lot of energy and remove organic matter such as humic acid in the sludge that can be complexed, solidified and interconnected. The heavy metals in the sludge cannot be effectively solidified, and the sintering process of organic matter may also produce toxic and harmful substances such as dioxins; the second is the non-burning method, which is to add other curing agents after dehydrating the sludge, add water and mix evenly, and then press and form it, such as a reservoir sludge non-burning brick and its preparation method (CN117185733A), a cast-in-place pile foundation mud rapid curing agent and its preparation method and application (CN118479806A). The curing agent added in the non-burning method is usually cement, gypsum, granulated blast furnace slag and other hydraulic cementitious materials, while the sludge does not participate in the cementing reaction in the system and only acts as a filler to be solidified. This unfired curing method relies on the hydration reaction time of hydraulic materials. The prepared solid bricks need to be cured for 28 days to reach the stacking and use strength. The production cycle is long and the compressive strength / dry density ratio is low. The sludge unfired blocks prepared in the above manner consume a large amount of existing resources, the sludge absorption capacity is small, the cost is high, and the market competitiveness is low. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a sludge unfired building block and a preparation method thereof, aiming to solve the technical problems that organic matter and heavy metals in the existing sludge cannot be effectively solidified, and the prepared building blocks have low strength, long production cycle and high cost.
[0006] In a first aspect, the embodiment of the present application provides a sludge unfired building block, wherein the raw material components include 25 to 40 parts by weight of sludge powder; 15-32.5 parts of blast furnace slag; 15-25 parts of fly ash; 20~30 parts of machine-made sand; An activator, the activator comprising 3.8-7.6 parts of a strong base activator and 5.8-15 parts of a weak base activator; 10~20 parts of water.
[0007] In the technical solution of the embodiment of the present application, an alkali excitation technology is used to release the silicon-aluminum minerals and metal cations in the blast furnace slag and fly ash in a strong alkaline environment to participate in the hydration reaction of the gel phase. Subsequently, the large amount of metal cations released and introduced will attack the bonded oxygen of the inert silicon-aluminum minerals in the sludge, reduce the binding energy of the silicon-aluminum bonds in the sludge, and achieve the synergistic activation of the sludge by the blast furnace slag and fly ash, so that the silicon-aluminum minerals in the sludge are quickly dissolved, and the secondary hydration of aluminum and silicon monomers is generated to participate in the composition of the gel phase. At the same time, the released metal cations such as iron, magnesium, and potassium can also modify the mesh structure of the gel, making the gel phase more compact.
[0008] Preferably, the strong base activator includes one or both of sodium hydroxide and potassium hydroxide, and the weak base activator includes one or both of water glass and potassium silicate.
[0009] Preferably, the particle size of the sludge powder is 0.3~500μm. The main chemical components of the sludge powder include, by mass: 35~55 parts of SiO2, 15~25 parts of Al2O3, 10~20 parts of loss on ignition (LOI), 0~3 parts of K2O, 0~3 parts of CaO; and 0~3 parts of MgO.
[0010] Preferably, the fly ash is Class F fly ash with a particle size of 0.3-100 μm. Its main chemical components, by mass, include: 40-60 parts of SiO2, 25-35 parts of Al2O3, 3-6 parts of Fe2O3, 3-6 parts of CaO, and 0.5-3 parts of K2O.
[0011] Preferably, the blast furnace slag is S95 grade powder with a particle size of 0.3-60 μm. Its main chemical components, by mass, include: 30-50 parts of CaO, 25-35 parts of SiO2, 10-20 parts of Al2O3, and 5-10 parts of MgO.
[0012] Preferably, the particle size of the machine-made sand is 80-2000 μm.
[0013] In the technical scheme of the embodiment of the present application, the grading of raw materials is optimized by changing the ratio of silt, blast furnace slag, fly ash and machine-made sand, so that the unfired blocks are more dense, and the micro-aggregates (silt, blast furnace slag, fly ash) provide more hydration points, so that the hydration process of the gel phase is uniform and rapid. The addition of machine-made sand not only fills the gaps of coarse particles to make the system more compact, but also has a skeleton support effect and an interlocking effect. The compression resistance, flexural resistance, frost resistance and other properties of the silt unfired blocks are significantly improved.
[0014] In a second aspect, the present application provides a method for preparing a sludge unfired building block, comprising the following steps: S1. Remove impurities from the sludge and dry it until the moisture content is less than 5 parts, grind it to obtain sludge powder, and reduce and homogenize it; S2, mixing the sludge powder in step S1 with blast furnace slag, fly ash and machine-made sand to obtain a precursor; S3, mixing the precursor in step S2 with water and an activator to obtain a blank; S4, pressing the blank obtained in step S3 into a shape, and curing at a set temperature for 3 to 14 days after demoulding to obtain a sludge unfired building block.
[0015] Preferably, the sludge in step S1 is dried and then ground using a vibration grinder, and the rotation speed of the vibration grinder is 600-1500 rpm.
[0016] Preferably, the pressing pressure in step S4 is 10-20 MPa, and the holding time is 1-5 min.
[0017] Different from the existing technical solutions, the beneficial effects of this application include: 1. In this application, the strong base activator provides a strong alkalinity for the system, which promotes the rapid dissolution of active silicon and aluminum components in blast furnace slag and fly ash, and releases metal cations such as sodium, potassium, and magnesium; the exogenous active silicon provided by the weak base activator and the metal cations released by the system will attack the bonded oxygen of the inert silicon-aluminum minerals in the sludge, reduce the binding energy of the silicon-aluminum bonds in the sludge, and achieve the synergistic activation of the sludge by blast furnace slag and fly ash, so that the silicon-aluminum minerals in the sludge are quickly dissolved, and the secondary hydration of aluminum and silicon monomers participates in the composition of the gel phase, so that fly ash, blast furnace slag, and sludge synergistically participate in the hydration and cementation reaction, and the rapid self-consolidation of the sludge is achieved in the state of no burning, eliminating the need for the addition of cement curing agent. The above technology can solve the problems of low sludge utilization rate, large amount of cement consumption, and long production cycle in the prior art.
[0018] 2. This application optimizes the grading of raw materials by changing the ratio of silt, blast furnace slag, fly ash and machine-made sand, making the unfired blocks denser. The micro-aggregates (silt, blast furnace slag, fly ash) provide more hydration points, making the hydration process of the gel phase uniform and rapid. The addition of machine-made sand not only fills the gaps of coarse particles to make the system denser, but also has a skeleton support effect and an interlocking effect. The compression resistance, flexural resistance, and frost resistance of the silt unfired blocks are significantly improved.
[0019] 3. The sludge unfired bricks prepared by the present invention can realize rapid self-consolidation of sludge at room temperature. The 7d compressive strength of the prepared sludge unfired bricks is up to 35.8 MPa, and the compressive strength after 25 freeze-thaw cycles is 27.9 MPa. All performances meet the highest grade MU25 standard in "JC / T 422-2007 Non-sintered Garbage Tailings Bricks", and can be widely used in housing construction, wall materials and other fields.
[0020] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 This is the SEM-EDS image of the sludge unfired block in Example 1 of the present application. DETAILED DESCRIPTION
[0023] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0025] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0026] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0027] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0028] Silt is mainly composed of inert mineral phases such as quartz, feldspar, and mica, which have low activity and contain a certain amount of organic matter and heavy metals. At room temperature, a large amount of cementing materials need to be added to achieve a good solidification effect. In addition, the silt only acts as a filler in the system to be solidified, which limits the large-scale disposal and utilization of silt.
[0029] Secondly, the preparation cycle of the unfired curing method depends on the cement hydration reaction time. The prepared solid bricks need to be cured for 28 days to reach the stacking and use strength. The production cycle is long and the compressive strength / dry density ratio is low. These characteristics increase the preparation cost and cycle of sludge unfired blocks, limiting the large-scale industrial application of sludge unfired blocks.
[0030] In order to solve the technical problem that the organic matter and heavy metals in the existing sludge cannot be effectively solidified, and the prepared blocks have low strength and high cost, the present application provides a sludge unfired block and a preparation method thereof, wherein the dissolution and activation of silicon-aluminum minerals, organic matter, etc. in the sludge is achieved through the synergistic alkali excitation of blast furnace slag and fly ash, so that the sludge participates in the hydration reaction of the gel, and the rapid self-consolidation of the sludge is achieved in the unfired state, eliminating the addition of cement curing agent. The gradation of raw materials is optimized by changing the ratio of sludge, blast furnace slag, fly ash, and machine-made sand, so that the unfired blocks are more dense, and the compression resistance, flexural resistance, frost resistance and other properties are improved. The above technology can solve the problems of low sludge utilization rate, large amount of cement consumption, and long production cycle in the existing technology.
[0031] In a first aspect, the embodiment of the present application provides a sludge unfired building block, wherein the raw material components include 25 to 40 parts by weight of sludge powder; 15-32.5 parts of blast furnace slag; 15-25 parts of fly ash; 20~30 parts of machine-made sand; An activator, the activator comprising 3.8-7.6 parts of a strong base activator and 5.8-15 parts of a weak base activator; 10~20 parts of water.
[0032] Preferably, the strong base activator includes sodium hydroxide and / or potassium hydroxide, and the weak base activator includes water glass and / or potassium silicate.
[0033] In the technical scheme of the embodiment of the present application, the activator includes a strong base activator and a weak base activator. Strong base activators such as sodium hydroxide and potassium hydroxide can provide a strong alkaline environment for the system, and are the initiating factors of the hydration reaction of the gel phase, which can quickly dissolve the active silicon and aluminum components in blast furnace slag and fly ash; weak base activators such as water glass and potassium silicate can provide an alkaline environment while also being able to act as exogenous active silicon to regulate the Si / Al ratio of the gel phase and increase the amount of gel phase generated. The combined use of strong base activators and weak base activators provides the system with strong alkalinity, promotes the rapid dissolution of active silicon and aluminum components in blast furnace slag and fly ash, and releases metal cations such as sodium, potassium, and magnesium. The exogenous metal cations and those released by the system will attack the bonded oxygen of inert silicon-aluminum minerals in the sludge, reduce the binding energy of silicon and aluminum bonds in the sludge, and achieve the synergistic activation of the sludge by blast furnace slag and fly ash, so that the silicon-aluminum minerals in the sludge are quickly dissolved, and the secondary hydration of aluminum and silicon monomers participates in the composition of the gel phase, so that fly ash, blast furnace slag, and sludge synergistically participate in the hydration and cementation reaction; the introduced exogenous silicon also makes the microstructure of the gel phase denser, and the compression and flexural properties of the blocks are improved.
[0034] Strong alkali activators increase the alkalinity of sludge unfired blocks. In addition to being able to dissolve active silicon and aluminum faster, they can also provide a suitable pH value for the metabolism of organic matter by microorganisms. Under suitable temperature and environmental conditions, the organic matter in the sludge is converted into fulvic acid, which consumes excess alkali in the later stage of the reaction, preventing the negative reaction of alkali to the brick body, and also has good performance in water resistance and anti-freeze-thaw cycles. The organic matter in the sludge is used to participate in the reaction, strengthen the self-consolidation of the sludge in the unfired state, eliminate the addition of other curing agents, and use the characteristics of the alkali activating system to shorten the preparation cycle, so that the mechanical properties of the sludge unfired blocks meet the national standards.
[0035] Preferably, the particle size of the sludge powder is 0.3-500 μm, and the main chemical components of the sludge powder include: 35-55 parts of SiO2, 15-25 parts of Al2O3, 10-20 parts of LOI, 0-3 parts of K2O, 0-3 parts of CaO; and 0-3 parts of MgO.
[0036] Preferably, the fly ash is Class F fly ash with a particle size of 0.3-100 μm. Its main chemical components, by mass, include: 40-60 parts of SiO2, 25-35 parts of Al2O3, 3-6 parts of Fe2O3, 3-6 parts of CaO, and 0.5-3 parts of K2O.
[0037] Preferably, the blast furnace slag is S95 grade powder with a particle size of 0.3-60 μm. Its main chemical components are as follows: 30-50 parts by mass, 25-35 parts by mass, 10-20 parts by mass, and 5-10 parts by mass.
[0038] In the technical solution of the embodiment of the present application, the calcium in the blast furnace slag can accelerate the hardening of the slurry by providing nucleation sites for the hydration products, and Ca 2+ Will react with [SiO4] in the system 4- and [AlO4] 5- Combined to form CSH or C-(A)-SH gel enriches the gel phase of the alkali-activated system, while Mg 2+ During the hydration process, it will react like Al 3+ Replace Si 4+ To promote the formation of NA(M)-SH gel phase.
[0039] Preferably, the particle size of the machine-made sand is 80-2000 μm.
[0040] In the technical scheme of the embodiment of the present application, the particle size ratio of the raw materials and the composition structure of the gel phase are adjusted by adjusting the proportion of sludge powder, blast furnace slag, fly ash and machine-made sand. Sludge powder, blast furnace slag and fly ash belong to the category of micro-aggregates, and have a nucleation effect, so that the hydration products are evenly distributed in the entire interface transition zone. There are also differences in particle grading between the three. Changing the proportion can improve the particle grading, improve the self-compacting system, and reduce the pore structure in the pressed blocks. The addition of machine-made sand introduces large particle grading into the system, which can form a skeleton to resist external loads and internal stresses, has a skeleton support effect and an interlocking effect, and improves the compression and flexural properties of the blocks. At the same time, the addition of machine-made sand reduces the amount of binder used, and the reduction of the gel phase with a high water content and a large expansion coefficient further improves the freeze-thaw resistance of the sludge unfired blocks.
[0041] In a second aspect, the present application provides a method for preparing a sludge unfired building block, comprising the following steps: S1. Remove impurities from the sludge and dry it until the moisture content is less than 5 parts, grind it to obtain sludge powder, and reduce and homogenize it; S2, mixing the sludge powder in step S1 with blast furnace slag, fly ash and machine-made sand to obtain a precursor; S3, mixing the precursor in step S2 with water and an activator to obtain a blank; S4, pressing the blank obtained in step S3 into a shape, and curing at a set temperature for 3 to 14 days after demoulding to obtain a sludge unfired building block.
[0042] Preferably, the sludge in step S1 is dried and then ground using a vibration grinder, and the rotation speed of the vibration grinder is 600-1500 rpm.
[0043] Preferably, the pressing pressure in step S4 is 10-20 MPa, and the holding time is 1-5 min.
[0044] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0045] 1. Preparation method Example 1 Embodiment 1 provides a sludge unfired building block and a preparation method thereof, comprising the following steps: S1. Pretreatment of raw materials: remove impurities from the sludge and dry it to a moisture content of less than 5 parts, grind it with a vibration grinder at a speed of 800 rpm for 0.5 minutes, and reduce and homogenize the powder obtained by the quartering method; S2. Mixing of raw materials: Mix sludge powder with blast furnace slag, fly ash and machine-made sand to obtain a precursor, wherein the components include 30 parts of sludge powder, 25 parts of blast furnace slag, 15 parts of fly ash and 30 parts of machine-made sand by weight; S3, preparation of blank: the precursor is mixed with water, sodium hydroxide and water glass to obtain a blank, and the mass fractions of each component are: 15 parts of water, 3.8 parts of sodium hydroxide, and 5.8 parts of water glass; S4. Forming and curing: the blank is filled into a steel mold, and a hydraulic testing machine is used to form the blank under a pressure of 10 MPa for 1 minute, and the blank is demoulded, cured at 60°C for 3 days, and then cured at room temperature for 7 days to obtain the final product.
[0046] Example 2 The difference between this embodiment and embodiment 1 is that: the sludge unfired building blocks and preparation method thereof in this embodiment, the mass fractions of the components in step S2 are: 25 parts of sludge powder, 25 parts of blast furnace slag, 15 parts of fly ash, and 35 parts of machine-made sand.
[0047] Example 3 The difference between this embodiment and embodiment 1 is that: the sludge unfired building blocks and preparation method thereof in this embodiment, the mass fractions of the components in step S2 are: 35 parts of sludge powder, 25 parts of blast furnace slag, 15 parts of fly ash, and 25 parts of machine-made sand.
[0048] Example 4 The difference between this embodiment and embodiment 1 is that: the sludge unfired building blocks and preparation method thereof of this embodiment, the mass fractions of the components in step S2 are: 40 parts of sludge powder, 32.5 parts of blast furnace slag, 7.5 parts of fly ash, and 20 parts of machine-made sand.
[0049] Example 5 The difference between this embodiment and embodiment 1 is that: the sludge unfired building blocks and preparation method thereof in this embodiment, the mass fractions of the components in step S2 are: 40 parts of sludge powder, 15 parts of blast furnace slag, 25 parts of fly ash, and 20 parts of machine-made sand.
[0050] Example 6 The difference between this embodiment and embodiment 1 is that: in the sludge unfired building blocks and preparation method thereof of this embodiment, the mass fractions of the components in step S3 are: 15 parts of water, 7.6 parts of sodium hydroxide, and 5.8 parts of water glass.
[0051] Comparative Example 1 The difference between this comparative example and Example 1 is that: in the sludge unfired building block and the preparation method thereof of this comparative example, water glass is not added in step S3.
[0052] Comparative Example 2 The difference between this comparative example and Example 1 is that in the sludge unfired building blocks and the preparation method thereof of this comparative example, no sodium hydroxide is added in step S3.
[0053] Comparative Example 3 The difference between this comparative example and Example 1 is that: in the sludge unfired building blocks and preparation method thereof of this comparative example, the mass fractions of the components in step S2 are: 40 parts of sludge powder, 40 parts of blast furnace slag, 20 parts of machine-made sand, and no fly ash is added.
[0054] Comparative Example 4 The difference between this comparative example and Example 1 is that: in the sludge unfired building blocks and preparation method thereof of this comparative example, the mass fractions of the components in step S2 are: 40 parts of sludge powder, 40 parts of fly ash, and 20 parts of machine-made sand, and no blast furnace slag is added.
[0055] Comparative Example 5 The difference between this comparative example and Example 1 is that: in the sludge unfired building blocks and preparation method thereof of this comparative example, the mass fractions of the components in step S2 are: 60 parts of sludge powder, 25 parts of blast furnace slag, 15 parts of fly ash, and no machine-made sand is added.
[0056] 2. Test Method 1. The compressive strength test of silt unfired blocks is carried out using a press machine according to GB / T4111-2013 "Test methods for concrete blocks and bricks".
[0057] 2. The flexural strength test of silt unfired blocks is carried out in accordance with GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" using a press machine with a loading speed of 0.08MPa / s.
[0058] 3. The water absorption test of silt unfired blocks is carried out in accordance with GB / T4111-2013 "Test methods for concrete blocks and bricks".
[0059] 4. The softening coefficient test of silt unfired blocks is carried out in accordance with GB / T4111-2013 "Test methods for concrete blocks and bricks".
[0060] III. Analysis of test results of various embodiments and comparative examples Figure 1This is the SEM-EDS image of the sludge unfired building block in Example 1 of the present application. It can be seen from the scanning electron microscope photo that the prepared unfired building block has a dense structure, and a large amount of gel phase is generated to glue the raw material particles together, and there are no obvious structural defects such as pores and cracks. The energy spectrum surface scan results show that the Si, Al, Na, Ca, and O elements show the characteristics of synchronous distribution, indicating that the main composition of the gel phase is (N, C)-ASH, and the hybrid symbiosis of sodium and calcium gel makes the gel phase denser. The compressive strength, flexural strength, water absorption rate and softening coefficient of the sludge unfired building blocks prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were tested, and the test results are shown in Table 1 below: Table 1 Performance test results of sludge unfired building blocks prepared in different embodiments and comparative examples
[0061] From the performance test results of the sludge unfired blocks of Example 1 in Table 1, it can be seen that the 7d compressive strength of the unfired blocks prepared by the method of the present application is up to 35.8 MPa, and the compressive strength after 25 freeze-thaw cycles is 27.9 MPa. All performances meet the standards of the highest grade MU25 in "JC / T 422-2007 Non-sintered Waste Tailings Bricks".
[0062] The mass fractions of machine-made sand in Examples 1 to 3 and Comparative Example 5 are 30 parts, 35 parts, 25 parts and 0, respectively. It can be seen from Table 1 that the flexural strength of Example 2 is lower than that of Example 1, and the flexural strength of Example 2 is higher than that of Example 1. It can be seen that when the amount of machine-made sand is too much, the interlocking effect is enhanced, and the uniformly distributed machine-made sand can effectively hinder the propagation of cracks and increase the flexural strength of the block. However, at the same time, the reduction of sludge components weakens the filling effect and nucleation effect of fine particles, and the increase of microporous structure and the decrease of density lead to a decrease in the compressive strength of the block; the compressive strength and flexural strength of Example 3 are slightly lower than those of Example 1. In Comparative Example 5, no machine-made sand is added, and the compressive strength and flexural strength are greatly reduced, indicating that when the amount of sludge is too much, the supporting effect and interlocking effect of the machine-made sand aggregate are weakened, and the compressive and flexural strengths of the block are reduced. When the ratio of sludge to machine-made sand is appropriate, a continuous and dense particle gradation can be formed to improve the various properties of the unfired blocks.
[0063] The mass fractions of fly ash in Examples 1 and 4 are 15 parts and 7.5 parts respectively, and no fly ash is added in Comparative Example 3. It can be seen from Table 1 that the compressive strength of the blocks in Example 4 is slightly lower than that in Example 1, and the compressive strength of the blocks in Comparative Example 3 is significantly lower than that in Example 1, indicating that when the fly ash dosage is too small, the aluminum component in the alkali-activated system is low, the Si / Al ratio deviates from the optimal range, the three-dimensional network structure of the gel is unstable, and the performance of the sludge unfired blocks is reduced.
[0064] The mass fractions of blast furnace slag in Examples 1 and 5 are 25 parts and 15 parts respectively, and no blast furnace slag is added in Comparative Example 4. As can be seen from Table 1, the compressive strength and flexural strength in Example 5 and Comparative Example 4 are both reduced, indicating that when the amount of blast furnace slag is too small, the calcium and magnesium components in the system are reduced, which will lead to the inert silicon-aluminum minerals in the sludge not being fully activated, resulting in reduced performance of the block. The appropriate ratio of fly ash and blast furnace slag can form a variety of gel symbiotic, stable, and dense microstructures, and the performance of the block is enhanced.
[0065] Example 6 and Comparative Examples 1-2 show the effects of the type and amount of activators on the performance of the blocks: agents such as sodium hydroxide and potassium hydroxide can provide a strong alkaline environment for the system and are the initiating factors for the hydration reaction of the gel phase; agents such as sodium silicate and potassium silicate provide weak alkalinity and cannot dissolve the active components quickly, but can act as exogenous active silicon to regulate the Si / Al ratio of the gel phase and increase the amount of gel phase generated; the combined use of sodium hydroxide and water glass provides a strong alkalinity for the system, which promotes the rapid dissolution of active silicon and aluminum components, and releases metal cations such as sodium, potassium, and magnesium. The exogenous and released large amounts of metal cations will attack the silicon and aluminum components in the sludge, reduce the binding energy of the chemical bonds, and achieve the synergistic activation of the sludge by blast furnace slag and fly ash under the alkaline activation system. The introduced exogenous silicon also makes the microstructure of the gel phase more compact, and the compression and flexural properties of the blocks are improved.
[0066] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A sludge unfired building block, characterized in that: The raw material components include 25-40 parts by weight of sludge powder; 15-32.5 parts of blast furnace slag; 15-25 parts of fly ash; 20~30 parts of machine-made sand; An activator, wherein the activator comprises 3.8 to 7.6 parts of a strong base activator and 5.8 to 15 parts of a weak base activator; 10~20 parts of water.
2. The silt unfired block according to claim 1, characterized in that: The strong base activator includes one or both of sodium hydroxide and potassium hydroxide, and the weak base activator includes one or both of water glass and potassium silicate.
3. The sludge unfired building block according to claim 1, characterized in that: The particle size of the sludge powder is 0.3-500 μm. The main chemical components of the sludge powder include, by mass: 35-55 parts of SiO2, 15-25 parts of Al2O3, 10-20 parts of LOI, 0-3 parts of K2O, 0-3 parts of CaO, and 0-3 parts of MgO.
4. The silt unfired block according to claim 1, characterized in that: The fly ash is Class F fly ash with a particle size of 0.3-100 μm. The main chemical components, by mass, include: 40-60 parts of SiO2, 25-35 parts of Al2O3, 3-6 parts of Fe2O3, 3-6 parts of CaO, and 0.5-3 parts of K2O.
5. The sludge unfired building block according to claim 1, characterized in that: The blast furnace slag is S95 grade powder with a particle size of 0.3-60 μm. Its main chemical components, by mass, include: 30-50 parts of CaO, 25-35 parts of SiO2, 10-20 parts of Al2O3, and 5-10 parts of MgO.
6. The silt unfired block according to claim 1, characterized in that: The particle size of the machine-made sand is 80-2000 μm.
7. A method for preparing a sludge unfired building block according to any one of claims 1 to 6, characterized in that: The steps include: S1. Remove impurities from the sludge and dry it until the moisture content is less than 5 parts, grind it to obtain sludge powder, and reduce and homogenize it; S2, mixing the sludge powder in step S1 with blast furnace slag, fly ash and machine-made sand to obtain a precursor; S3, mixing the precursor in step S2 with water and an activator to obtain a blank; S4, pressing the blank obtained in step S3 into a shape, and curing at a set temperature for 3 to 14 days after demoulding to obtain a sludge unfired building block.
8. The method for preparing the sludge unfired building block according to claim 7, characterized in that: The sludge in step S1 is dried and then ground using a vibration grinder, and the rotation speed of the vibration grinder is 600-1500 rpm.
9. The method for preparing the sludge unfired building block according to claim 7, characterized in that: The pressure of the pressing molding described in step S4 is 10-20 MPa, and the holding time is 1-5 min.
10. The method for preparing the sludge unfired building block according to claim 7, characterized in that: The curing temperature in step S4 is 15-90°C.
Citation Information
Patent Citations
Lake and reservoir sludge sintered brick and preparation method thereof
CN115286421A
Method for preparing sintered bricks by roasting river sludge at high temperature
CN116715507A
Reservoir sediment baking-free brick and preparation method thereof
CN117185733A
Rapid curing agent for cast-in-place pile foundation slurry as well as preparation method and application of rapid curing agent
CN118479806A
Inorganic-polymer mud solidification mortar and preparation method thereof
CN106082926A